The development of a theory informed behaviour change intervention to improve adherence to dietary and physical activity treatment guidelines in individuals with familial hypercholesterolaemia (FH) - F. J. Kinnear; E. Wainwright; J. E. Bourne; F. E. Lithander; J. Hamilton-Shield; A. Searle (BMC, 2020)
Abstract Background Familial hypercholesterolaemia (FH) is a genetic condition characterised by elevated levels of low-density lipoprotein cholesterol (LDL-C) and an increased risk of cardiovascular disease (CVD). Following dietary and physical activity guidelines could help minimise this risk but adherence is low. Interventions to target these behaviours are therefore required. A comprehensive understanding of the target behaviours and behaviour change theory should drive the process of intervention development to increase intervention effectiveness and scalability. This paper describes the application of a theoretical framework to the findings of a qualitative evidence synthesis (QES) to inform the content and delivery of an intervention to improve adherence to dietary and physical activity guidelines in individuals with FH. Methods The Behaviour Change Wheel (BCW) was used to guide intervention development. Factors influencing dietary and physical activity behaviours were identified from an earlier QES and mapped onto factors within the BCW. A comprehensive behavioural diagnosis of these factors was conducted through application of the theoretical domains framework (TDF). Using these data, the most appropriate intervention functions and behaviour change techniques (BCTs) for inclusion in the intervention were identified. Decision making was guided by evaluation criteria recommended by BCW guidance and feedback from individuals with FH. Results Factors influencing dietary and physical activity behaviours mapped onto twelve of the fourteen TDF domains, with seven intervention functions deemed suitable to target the domains' theoretical constructs. Twenty-six BCTs were identified as being appropriate for delivery within these functions and were included in the intervention. For instance, within the enablement intervention function, the BCT problem solving was incorporated by inclusion of a 'barriers and solutions' section. Guided by evaluation criteria and feedback from individuals with FH, the intervention will be delivered as an hour-long family-based appointment, followed up with four telephone calls. Conclusions The novel application of the BCW and TDF to the results of a QES has enabled the development of a theory and evidence informed behaviour change intervention. This systematic approach facilitates evaluation of the intervention as part of an ongoing feasibility trial. The transparent approach taken can be used to guide intervention development by researchers in other fields.